Antropological horizons of gender equality: from religious cannons to business challenges - Oleksenko, Roman; Олексенко, Роман Іванович; Олексенко, Роман Иванович; Ortina, Hanna; Ортіна, Ганна Володимирівна; Ортина, Анна Владимировна; Kolokolchykova, Iryna; Колокольчикова, Ірина Володимирівна; Колокольчикова, Ирина Владимировна; Syzonenko, Olena; Сизоненко, Олена Василівна; Сизоненко, Елена Васильевна (My University, 2018)
EN: Any religion in the world emphasizes the woman's femininity, namely an anthropological feature that does not require similarity with the functional features of her husband. However, in turn, it has the potential of a comprehensive development of the individual as a mother, and the realization of the role of women in society. The misconceptions that maternity lifts women's potential and suppresses their personal development causes a lot of controversial issues that lead to negative manifestations of gender inequality. Negative manifestations of the perception of false positions lead to terrible structural changes in society, ruin (or shake) the foundations of the laws of motherhood, have consequences of the aging of the nation, the loss of human spiritual humanism. Women lose the opportunity to feel like a mother and transfer their love of work to work as a child. Therefore, its main base anthropological identity is reduced to zero in this case and makes a woman "uncertain" gender, which will never find its place in society. The aim of the study.It based on the study of the anthropological horizons of gender inequality within the framework of religious canons and modern trends in the manifestation of business, the loss of anthropological value of women. The author's team has proved that each of the religions of the world pays much attention to women as mothers, their roles in society with exceptional abilities and special qualities. None of the religions does restrict women in revealing these abilities, but places anthropological peculiarity on the first place of a woman-mother, guardian of the family. Religion acts as a universal anthropological phenomenon, which reveals each individual essential element characteristic of every person and emphasizes its importance for society. UK: У статті досліджуються антропологічні горизонти гендерної нерівності в рамках релігійних канонів та сучасних тенденцій прояву бізнесу, втрати антропологічної цінності жінок. RU: В статье исследуются антропологические горизонты гендерного неравенства в рамках религиозных канонов и современных тенденций проявления бизнеса, потери антропологической ценности женщин.
Антропологічні горизонти гендерної нерівності: від релігійних канонів до бізнесових викликів
Антропологические горизонты гендерного неравенства: от религиозных канонов до бизнесовых вызовов
Keywords: gender; inequality; woman; women's potential; business; society; public consciousness; religion; гендер; нерівність; жінка; жіночий потенціал; бізнес; суспільство; суспільна свідомість; релігія; неравенство; женщина; женский потенциал; бизнес; общество; общественное сознание; религия